HUMAN RESOURCE COMPETENCE TOWARDS INDONESIA’S MICRO & SMALL ENTERPRISES’ PERFORMANCE - Martin Sandyawan; Catharina Badra Nawangpalupi; Gandhi Pawitan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Micro and Small Enterprises (MSEs) have a huge role in Indonesia's economic performance. Ranging from GDP contribution to job opportunities creation. The majority of Indonesian companies belongs in the MSE category, reaching 99,89% of all companies in Indonesia. Therefore it is very important to know which factor affects MSEs' performance the most. Great performance by these MSEs will lead to greater national economic performance. Studies conducted with similar research methodologies show that one of the most important factors toward MSEs' performance is its human resources. To assess the importance of human resources toward MSEs' performance in Indonesia, we use secondary data from Indonesia's Central Bureau of Statistics on MSEs' during 2017. We use MSEs' profit as a way to measure its performance and represent human resource competence using education level and worker training programs both on the managerial/owner level and worker level from the available data. Data analysis showed that general education of manager/owner or workers does not affect MSEs' profit significantly but training programs on both managerial/owner and worker level have significant impact on MSEs' profit compared to MSEs' with no training except for managerial training.